2015
DOI: 10.1166/jnn.2015.11197
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Performances of Yttrium Doped Li3V2–XYX(PO4)3/C Cathode Material for Lithium Secondary Battery

Abstract: We report the development of hydroxyapatite nanoparticle (HAp NP)-functionalized hetero-graft materials (HGMs) for dental applications. These HGMs were prepared by attaching platelet-, needle-, and sphere-shaped HAp NPs to the surface of xenograft materials through chemical conjugation. Although all three HAp NPs contributed to increase the surface area of bone graft material (BGM), the shape of the HAp NPs was a determining factor. Platelet HAp NPs were most effective, because they caused a 48.9% increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Physicochemical properties are even more important for xenografts [ 2 ]. Xenografts have clear advantages, as they can be mass-produced in large quantities at relatively affordable processing costs.…”
Section: Introductionmentioning
confidence: 99%
“…Physicochemical properties are even more important for xenografts [ 2 ]. Xenografts have clear advantages, as they can be mass-produced in large quantities at relatively affordable processing costs.…”
Section: Introductionmentioning
confidence: 99%
“…The poor electrical conductivity of this material (∼10 −8 S.cm −1 ) can be directly linked to the large separation between V ions in the framework of LVP due to the PO 4 tetrahedra. 22,23 To enhance the overall electrochemical performance of LVP, several approaches have been adopted, such as carbon coating, 24 reducing the size of the particles [25][26][27] and most commonly used, cationic doping, such as divalent cation doping (Mg 2+ , Mn 2+ , Ni 2+ , … ), [28][29][30] trivalent (Fe 3+ , Al 3+ , Cr 3+ , Y 3+ , … ) [31][32][33][34][35] and tetravalent cation doping (Sn 4+ , Zr 4+ , Ge 4+ , Ti 4+ , … ). 23,[36][37][38][39][40][41] According to these studies, cation doping was found to influence the particle size, the electrical conductivity, structural stability and Li + mobility of the material, all of which have a significant impact on its electrochemical performance rated by the capacity, the energy density, and the cycling stability.…”
mentioning
confidence: 99%